Serum Copper and Zinc Concentrations In Leprosy and Tuberculosis - Erel, Özcan; Gürel, Mehmet Salih; İlhan, Necip; Özdemir, Yüksel (Fırat University, 2001)
Serum copper and zinc concentrations were determined in 46 leprosy and 85 pleural tuberculosis patients and compared with those of 77 healthy subjects. Diagnosis was performed by clinical and laboratory findings. Serum copper and zinc concentrations were determined by colorimetric methods. Variance analysis and correlation analysis tests were used for statistical evaluation. Serum copper concentrations in leprosy patients were found as 135.61± 24.67 µg/dl, in patients with tuberculosis 167.28±37.54 µg/dl and, in healthy subjects 113.94±20.39 µg/dl Serum zinc concentration in leprosy patients were determined as 108.70±27 .92 µg/dl, in patients with tuberculosis 99.62 ±21.48 µg/dl, and in healthy subjects 117.30 ±21.42 µg/dl The increase in copper and decrease in zinc levels of serum may be attributed to the acute phase reactions of the host against infectious or noninfectious inflammations. Leprosy and tuberculosis have got similar characteristics related to their etiology, immunology and cytopathological aspects. The determination of serum copper and zinc concentrations may provide a new approach for evaluation of the immune status of leprosy and tuberculosis.

Serum bakır ve çinko konsantrasyonları, 46 lepra ve 85 tüberküloz plörezili (Tbc) hastada saptanmış ve 77 sağlıklı bireyin sonuçlarıyla karşılaştırılmıştır. Tanı, klinik ve laboratuvar bulguları ile gerçekleştirilmiştir. Serum bakır ve çinko konsantrasyonları kolorimetrik yöntemlerle ölçülmüştür. Elde edilen veriler varyans analizi ve korelasyon analizi testleriyle değerlendirilmiştir. Serum bakır konsantrasyonu lepra hastalarında 135.61Mg/dl ±24.67 µg/dl Tbc hastalarında 167mg/dl 28 ± 37.54 µg/dl sağlıklı bireylerde ise 113.94±20,39 µ g/dl'dir. Serum çinko konsantrasyonu lepra hastalarında 108.71± 27.92µg/dl , Tbc hastalarında 99.62 ± 21.48 µg/dl sağlıklı bireylerde 117.30±21.42 µg/dl olarak bulunmuştur. Bu makro iz elementlerin konsantrasyonlarındaki değişiklikler enflamasyona karşı konağın geliştirdiği akut faz reaksiyonuna bağlı olabilir. Lepra ve tüberküloz etiyolojik, immünololojik ve sitopatolojik olarak birbirine benzeyen kronik, enfeksiyöz ve granülamatöz hastalıklardır .Serum bakır ve çinko düzeyleri lepra ve tüberkülozda konağın antienflamatuar ve immüno cevabının değerlendirilmesinde ve izlenmesinde yeni bir yaklaşım sağlayabilir.
LEPRA VE TÜBERKÜLOZDA SERUM BAKIR VE ÇİNKO DÜZEYLERİ